2020
DOI: 10.1371/journal.ppat.1008753
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the immunogenic landscape of near-native HIV-1 envelope trimers in non-human primates

Abstract: The induction of broad and potent immunity by vaccines is the key focus of research efforts aimed at protecting against HIV-1 infection. Soluble native-like HIV-1 envelope glycoproteins have shown promise as vaccine candidates as they can induce potent autologous neutralizing responses in rabbits and non-human primates. In this study, monoclonal antibodies were isolated and characterized from rhesus macaques immunized with the BG505 SOSIP.664 trimer to better understand vaccine-induced antibody responses. Our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 82 publications
10
78
1
Order By: Relevance
“…S13). RM20C does not neutralize BG505 virus as an immunoglobulin G (IgG) but can weakly neutralize as a Fab, consistent with the hypothesis that the disposition of the second Fab arm and Fc can sterically inhibit access to the base epitope on intact virions ( 26 ). Therefore, although the base epitope shared by two known bnAbs and one autologous neutralizing Fab is a bona fide site of vulnerability, access is highly constrained.…”
Section: Resultssupporting
confidence: 61%
“…S13). RM20C does not neutralize BG505 virus as an immunoglobulin G (IgG) but can weakly neutralize as a Fab, consistent with the hypothesis that the disposition of the second Fab arm and Fc can sterically inhibit access to the base epitope on intact virions ( 26 ). Therefore, although the base epitope shared by two known bnAbs and one autologous neutralizing Fab is a bona fide site of vulnerability, access is highly constrained.…”
Section: Resultssupporting
confidence: 61%
“…We also generated B cells expressing the base-specific non-NAb RM19R that was isolated from a BG505 SOSIP trimer-immunized macaque 36 . The exposed base of SOSIP trimers contains immunodominant non-NAb epitopes that may distract the immune response away from sites more favored to NAb induction 37 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that glycans on gp41 are underoccupied compared with glycans on gp120 when expressed as recombinant protein on both native-like SOSIP trimers ( Guttman et al, 2014 ; Depetris et al, 2012 ; Cao et al, 2018 ; Behrens et al, 2016 ) and uncleaved recombinant gp140 ( Pabst et al, 2012 ; Go et al, 2011 ). The N611 glycosylation site, which falls within region 5, has been directly shown to be underglycosylated depending on the Env isolate ( Cottrell et al, 2020 ; Cao et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, at least some of the Env-specific CD4 T cell responses are likely a result of suboptimal glycosylation on specific N-linked glycosylation sites. For example, N611 is thought to be underglycosylated in BG505 SOSIP Env trimers ( Cottrell et al, 2020 ), and N197 was directly shown to be underglycosylated in BG505 SOSIP ( Cao et al, 2018 ), although these results have yet to been shown in BG505 SOSIP trimer containing the MD39 trimer stabilizing mutations. The large CD4 T cell response to the underglycosylated gp41 region 5 trimer variants might not be recapitulated when immunizing with other Env constructs that have a much higher glycan occupancy at N611.…”
Section: Discussionmentioning
confidence: 99%